2015
DOI: 10.1093/ije/dyv293
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy history and risk of premenopausal breast cancer—a nested case-control study

Abstract: The divergent results with regard to parity and PBC risk when using sister and population controls suggest that the influence of childbearing may be modified by genotype. Selection bias when using different control groups must also be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 45 publications
1
12
2
Order By: Relevance
“…The literature on breast cancer risk in women with a history of preeclampsia is inconsistent. Some studies have reported an inverse association, one a positive association and others, including meta‐analyses, reported no association . Only two studies, both of case–control design, investigated the association between preeclampsia history and breast cancer by menopausal status, with one reporting a decreased risk of postmenopausal but not premenopausal breast cancer and the other no association in either group, contrary to our findings of a reduced risk of premenopausal but not postmenopausal breast cancer.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The literature on breast cancer risk in women with a history of preeclampsia is inconsistent. Some studies have reported an inverse association, one a positive association and others, including meta‐analyses, reported no association . Only two studies, both of case–control design, investigated the association between preeclampsia history and breast cancer by menopausal status, with one reporting a decreased risk of postmenopausal but not premenopausal breast cancer and the other no association in either group, contrary to our findings of a reduced risk of premenopausal but not postmenopausal breast cancer.…”
Section: Discussioncontrasting
confidence: 99%
“…5,6 It has been hypothesised that preeclampsia might therefore be associated with a decreased risk of maternal breast cancer. 7 Evidence from previous studies has been inconsistent, however, with studies reporting negative, [7][8][9][10][11] positive 12 or no [13][14][15][16][17] association with breast cancer risk. Few studies have been of prospective design and the studies have often not been able to adjust for potential confounders.…”
Section: Introductionmentioning
confidence: 99%
“…In theory, late-pregnancy stimuli that transform the breast tissue to a stage represented by a lowered breast cancer risk could originate from both the mother and the fetus. However, findings by us and others provide little evidence for a fetal involvement since infant sex 23 , infant absolute birthweight 10 , 24 or, as we show, fetal growth restriction and vital status of the infant at birth do not influence the long-term breast cancer risk.…”
Section: Discussioncontrasting
confidence: 93%
“…[15][16][17] This trend among premenopausal women may reflect a change in risk factors, including later age at first childbirth, increased oral contraceptive use and earlier age at menarche. [18][19][20][21][22][23][24][25][26][27][28][29] A similar trend was noted for colorectal and pancreatic cancer, which has also been seen in the US. 30,31 These findings solidify the need for public health measures and interventions that address weight management and are aimed at younger adults.…”
Section: Discussionmentioning
confidence: 55%